Perspectives of clinical stakeholders and patients from four VA liver clinics to tailor practice facilitation for implementing evidence-based alcohol-related care - Elena M. Soyer; Madeline C. Frost; Olivia V. Fletcher; George N. Ioannou; Judith I. Tsui; E. Jennifer Edelman; Bryan J. Weiner; Rachel L. Bachrach; Jessica A. Chen; Emily C. Williams (Addiction Science & Clinical Practice, 2024)
Abstract Background Unhealthy alcohol use (UAU) is particularly dangerous for people with chronic liver disease. Liver clinics may be an important setting in which to provide effective alcohol-related care by integrating evidence-based strategies, such as brief intervention and medications for alcohol use disorder. We conducted qualitative interviews with clinical stakeholders and patients at liver clinics in four Veterans Health Administration (VA) medical centers to understand barriers and facilitators of integrating alcohol-related care and to support tailoring of a practice facilitation implementation intervention. Methods Data collection and analysis were guided by the Consolidated Framework for Implementation Research (CFIR). Interviews were transcribed and qualitatively analyzed using a Rapid Assessment Process (RAP) guided by the CFIR. Results We interviewed 46 clinical stakeholders and 41 patient participants and analyzed findings based on the CFIR. Clinical stakeholders described barriers and facilitators that ranged from operations/clinic resource-based (e.g., time and capacity, desire for additional provider types, referral processes) to individual perspective and preference-based (e.g., supportiveness of leadership, individual experiences/beliefs). Patient participants shared barriers and facilitators that ranged from relationship-based (e.g., trusting the provider and feeling judged) to resource and education-based (e.g., connection to a range of treatment options, education about impact of alcohol). Many barriers and facilitators to integrating alcohol-related care in liver clinics were similar to those identified in other clinical settings (e.g., time, resources, role clarity, stigmatizing beliefs). However, some barriers (e.g., fellow-led care and lack of integration of liver clinics with addictions specialists) and facilitators (e.g., presence of quality improvement staff in clinics and integrated pharmacists and behavioral health specialists) were more unique to liver clinics. Conclusions These findings support the possibility of integrating alcohol-related care into liver clinics but highlight the importance of tailoring efforts to account for variation in provider beliefs and experiences and clinic resources. The barriers and facilitators identified in these interviews were used to tailor a practice facilitation implementation intervention in each clinic setting.